Subgrains, micro-twins and dislocations characterization in monolike Si using TEM and in-situ TEM. (2018) - Lantreibecq, A.; Monchoux, J.-Ph.; Pihan, E.; Marie, B.; Legros, M.
Abstract: A critical aspect in the development of mono-like Silicon for photovoltaic (PV) application lies in the control of its defect microstructure. While micro-twins do not seem to represent a major concern regarding electrical activity, some dislocations and low angle grain boundaries need to be avoided in the growing process because of their recombination properties. Here, we have studied how these defects grow and interact together in order to understand what are the mechanisms responsible for their presence in the cast ingots. We show that, in our specific convex liquid-solid interface growth mode, micro-twins probably originate from this interface while dislocations and subgrains build up both by epitaxy at the solid liquid interface and through dislocation-boundary interactions in the solidified region. Post-growth TEM characterization allowed identifying constitutive dislocations of some subgrain boundaries for the case of [001] seeds. In-situ TEM straining of Si at high temperature also allowed measuring dislocation mobility at several temperatures. Those are compared to the dislocation velocities in pure Czochralski Si found in literature.